A conceptual framework for understanding pre-entry factors influencing first-year university experience - Pather, S; Chetty, R (South African Journal of Higher Education, 2016)
Student cohorts entering universities in South Africa have become more diverse; making the first-year experience more complex to understand. In order to address these challenges, a conceptual framework that accounts for the situated circumstances of the diverse students entering higher education is explored. The conceptual framework integrates key concepts from Bourdieu’s (1984; 1990) conceptual tools and Tinto’s (1975; 1993) student integration model. The framework facilitates in-depth understanding of pre-entry factors influencing first-year experience. To test the efficacy of the conceptual model, an analysis of one student’s negotiations through her first-year university experience is reported. This paper highlights the utility of this framework, identifying the manner in which pre-entry factors from the participant’s situated context assisted in explaining how habitus shaped her first-year experience and academic performance. The themes identified: determination, motivation and self-resilience, helped understand why this participant made decisions that influenced her social and academic integration at university. Study outcomes suggest some initial insights and a starting point to influence actions that might improve university transition and integration of students from relatively disadvantaged backgrou